An Experimental Study of Vermicomposting with Earthworm (Eisenia Foetida) Growth in Edible Mushrooms Wastes - Fataei, E.; Majd, K. Hashemi; Zakeri, F.; Jeddi, E. Akbari (International Journal of Bio-resource and Stress Management, 2023)
Every year mushroom wastes are produced in big volumes from edible mushroom production industries. Vermicomposting technology is using earthworms as versatile natural bioreactors for effective recycling of organic wastes of the soil and an environmentally acceptable means of converting waste into nutritious composts for crop production. This study was undertaken to use earthworms (Eisenia foetida) in vermicomposting on edible mushroom’s wastes. The Randomized block design with three treatments in Kimia, Sabalan and Artashahr mushroom production industries were selected and four replications were applied for treatments. The total biomass of earthworms was estimated by counting the number of adults, juveniles and cocoons from each replication .The number of adult and mature worms, egg capsules and wet weight of earthworms were recorded in one month intervals (totally in five months). Vermicomposting carried out by these worms in four months in spite of delay in their establishment in mushroom wastes. The worms wet weight, their number and the number of capsules were increased up to fourth month and then decreased. The produced vermicompost had suitable properties for amending soil.